EVOLUSI SUKUK (OBLIGASI SYARIAH): TANTANGAN DAN PROSPEK MASA DEPAN DI TAPAL KUDA JAWA TIMUR - Zaenol Hasan; Saini; Ridan Muhtadi (TERAJU: Jurnal Syariah dan Hukum, 2024)
This study aims to understand the challenges and constraints in the evolution of Islamic bonds and explore the challenges that have been identified. aims to provide insights into the dynamics of sukuk and identify key challenges. The research method used in this study is a qualitative case study approach. This study uses purposely selected informants. Data were collected through observation, in-depth interviews and documentation to gain an in-depth understanding of this phenomenon. The data was analyzed using the Miles and Huberman data analysis technique, which includes data reduction, data display, and verification, resulting in a comprehensive conclusion about the challenges and future prospects of sukuk (Islamic bonds). The research results in this study produce several causes of challenges and obstacles to the evolution of sukuk (Islamic bonds) in the form of non-uniformity of sharia principles that must be used as guidelines and the complexity of the transaction structure. The study concludes that the evolution of sukuk (Islamic bonds) is faced with significant challenges such as public perception and regulatory complexity, which affect the development of this financial instrument. Nonetheless, the future prospects of sukuk remain promising with increased understanding of Shariah principles and efforts to improve the regulatory infrastructure. To achieve the full potential of sukuk, strong collaboration between market participants, regulators and the public is required to overcome these challenges and capitalize on opportunities to support inclusive and sustainable economic growth.